Efeito da suplementação alimentar com leucina no colágeno cardíaco e na função ventricular esquerda associada ao uso da doxorrubicina em ratos Wistar - Haddad, Eduardo Gaspareto (2020)
Introduction: Anti-cancer treatments using doxorubicin have the side effect of inducing cardiotoxicity, which may manifest itself years after the end of the treatment cycle. Among the different expressions of cardiotoxicity, ventricular dysfunction and the onset of myocardial fibrosis are prominent features. Some strategies to contain and/or reverse this framework have been proposed. Leucine is an essential amino acid that stimulates protein synthesis, but its exact role in doxorubicin-induced cardiotoxicity is not fully known. Objective: To verify the effects of dietary leucine supplementation on cardiac collagen production and its relationship with left ventricular function after exposure to doxorubicin in Wistar rats. Material and Methods: The experiment was conducted at REBIR-UFU and lasted 42 days. Thirty-six male Wistar rats weighing between 250 and 300 grams were randomly divided into four groups: Control (C n = 8), Doxorubicin (D n = 10), Leucine (L n = 8) and Doxorubicin + Leucine. (DL n = 10). Groups C and D were offered a standard diet and groups L and LD received a diet enriched with 5% leucine. Groups D and LD received intraperitoneal injections of doxorubicin three times a week over two weeks until the cumulative dose of 7.5 mg / kg was reached. Groups C and L received saline solution intraperitoneally, similar in volume to that used as a doxorubicin vehicle. At the end of the experimental period, the animals were anesthetized and submitted to transthoracic echocardiography for left ventricular evaluation. After euthanasia, left ventricular sections were obtained for histological analysis and quantification of collagen staining by Picrosirius red. The results were recorded photographically (10X objective, 10X eyepiece) under a Nikon eclipse® TS 100 microscope. For statistical comparison between experimental groups, the univariate generalized linear model complemented by Tukey test was used. Statistical significance was established for p values <0.05. Results: There was an increase in total collagen in group D compared to C, L and LD (4.00 + 2.68 x 2.37 ± 1.50 x 1.94 + 1.34 x 2.50 + 1.61 (p = 0.01). Left ventricular ejection fraction was higher in the LD group than in the D group (72.75 ± 2.87 x 65.37 ± 2.87; p = 0.01). Conclusion: Dietary supplementation with 5% leucine attenuated total collagen accumulation and preserved left ventricular function when administered in combination with doxorubicin in Wistar rats.